Exciton dynamics and annihilation in WS2 2D semiconductors1. Issue 16 (28th April 2015) - Yuan, Long; Huang, Libai
<x xml:space="preserve">Abstract</x> We systematically investigate the exciton dynamics in monolayered, bilayered, and trilayered WS2 two-dimensional (2D) crystals by time-resolved photoluminescence (TRPL) spectroscopy.